Application of Simple Additive Weighting (SAW) Method in Decision Support System for Selecting Study Programs At The University Of Papua - Fransiskus Jekson Rua; Dedi Iskandar Inan; Marlinda Sanglise; Ratna Juita; Lorna Yertas Baisa (G-Tech: Jurnal Teknologi Terapan, 2024)
To help prospective students choose a study program that suits their abilities and interests, it is necessary to design a decision support system. This system aims to facilitate the selection process of study programs for prospective students. This research aims to develop a decision support system that can help prospective students in choosing a study program at the Faculty of Engineering, University of Papua in an objective and structured manner. This study applies the Simple Additive Weighting method to facilitate the decision-making process by considering a number of relevant criteria. The evaluation is based on the following criteria: tuition fees, accreditation status, number of teaching staff and staff, and job prospects. The findings of the study revealed that the Informatics Engineering and Civil Engineering Study Programs, both at the S1 level, obtained the highest identical preference value, namely 1, outperforming other study programs. However, the best alternative is the S1 Informatics Engineering Study Program.